Misoginia e exaltação da mulher em obras literárias clássicas da Coroa de Aragão. - ALEXANDRE DOS SANTOS, ARMANDO (Scripta, 2021)
The process of valorization of the feminine condition, that presented a discreet and promising progress in the first half of the 13th century, regressed in the following centuries in a non-linear and uniform manner. At the same time that the so-called “amour courtois” developed in the upper strata of society and idealized women began to receive less brutal treatment than in earlier times, a mentality also developed, on a theoretical and psychological level, of contempt and condemnation of women. Two classic literary works of the Crown of Aragon give a very clear example of this contradictory duplicity. In “Lo Somni” (1399), one chapter is clearly and aggressively misogynistic, while exemplary women are celebrated and glorified in the other chapter. In “Curial e Gelfa” (c. 1448), the female role is notorious, but several passages are extremely critical of women, bordering on misogyny.